Caracterización cuantitativa de las producciones audiovisuales en cine y televisión en el departamento del Meta (Colombia) entre 2000 y 2025 (REVISTA NODO, 2025)
This article analyzes the evolution of film and television production in the Meta department (Colombia) between 2000 and 2025. Using a quantitative methodology, 85 technical records were systematized to identify trends in format, duration, genre, themes, circulation, and recognition. Short films dominated over feature films, with a significant presence of fiction and documentary productions focusing on everyday life, Llanero traditions, collective memory, and the armed conflict. The year 2019 marked a production peak, aligning with national audiovisual industry growth. Despite receiving awards at festivals such as Pele el Ojo and Crisol, most productions circulate only locally. A heavy dependence on public funding and limited national and international distribution were noted. The study concludes that audiovisual production in Meta has evolved toward more critical, diverse, and socially engaged narratives but requires comprehensive strategies to strengthen distribution, preservation, professional training, and the establishment of a regional audiovisual archive. Audiovisual media emerge as a key tool for symbolic territorial construction and memory-building in the post-conflict context.
Keywords: audiovisual production; regional cinema; television; short film; memory